Science and Technology Parks: laboratories of innovation for urban development - an approach from Brazil - Desiree Moraes Zouain; Guilherme Ary Plonski (Triple Helix, 2015)
A large part (85%) of Brazil's population lives in urban areas. Roughly half of these dwellers are located in large cities, defined as having 750,000 or more inhabitants. The urbanization trend is due to historical migration movements that occurred mostly before the recent phenomenon of globalization. Nevertheless, the growth of these urban centers is characterized by insufficient public policies capable of ensuring quality of life to its residents. The main assumption of this paper is that large cities may adopt as a strategy the establishment of laboratories of innovation focused on urban development. This effort requires the municipal leadership to organize ways for stimulating the citizens or at least some segments of the population to use creativity and knowledge in order to propose feasible innovative solutions to the serious urban problems they face. In Brazil, Science and Technology Parks (STPs) have assumed the role of laboratories of urban pertinent innovation in several cases. The aim of this research is to study STPs and their possible contribution to sustainable transformation of cities and regions in Brazil, a large, heavily populated and countrywide diverse upper-middle-income economy. The research question is: what makes STPs contribute to improving the quality of urban development? The methodology unfolds according to the following steps: (i) preliminary diagnosis, (ii) learning process - good practice studies; and (iii) feedback - key lessons - revisiting STP models. Based on a review of the Brazilian experience, this article points out that (i) STPs in different parts of the country have been actually functioning as laboratories of innovation that generate solutions applicable to urban development; (ii) as in high-income economies - mainly in the USA, where they originated in the 1950s, STPs in an upper-middle-income economy were capable of rapidly becoming hubs of innovation ecosystems in diverse cities and regions (it should be noted that, with only a few earlier exceptions, the widespread emergence of STPs in Brazil is a phenomenon of the 2000s); and (iii) there is an essential need to use tools that assist STPs in the planning and coordination processes, in order to achieve a level of institutional articulation in the city or region that enables Triple Helix-alike innovation ecosystems to lever sustainable urban transformation.
Keywords: 330; Innovation policy; Innovation habitat; Regional development; Science and Technology Park; Urban development